The Correlation Between Busulfan Exposure and Clinical Outcomes in Chinese Pediatric Patients: A Population Pharmacokinetic Study - Xiaohuan Du; Xiaohuan Du; Chenrong Huang; Chenrong Huang; Ling Xue; Ling Xue; Zheng Jiao; Min Zhu; Jie Li; Jun Lu; Peifang Xiao; Xuemei Zhou; et al. (Frontiers Media S.A., 2022)
Aims: The aims of the study were to 1) establish a population pharmacokinetic (Pop-PK) model for busulfan in Chinese pediatric patients undergoing hematopoietic stem cell transplantation (HSCT) and then estimate busulfan exposure and 2) explore the association between busulfan exposure and clinical outcomes.Methods: A total of 128 patients with 467 busulfan concentrations were obtained for Pop-PK modeling using nonlinear mixed effect model (NONMEM) software. Sixty-three patients who received the 16-dose busulfan conditioning regimen were enrolled to explore the correlations between clinical outcomes and the busulfan area under the concentration-time curve (AUC) using the Cox proportional hazards regression model, Kaplan-Meier method and logistic regression.Results: The typical values for clearance (CL) and distribution volume (V) of busulfan were 7.71 L h−1 and 42.4 L, respectively. The allometric normal fat mass (NFM) and maturation function (Fmat) can be used to describe the variability in CL, and the fat-free mass (FFM) can be used to describe the variability in V. Patients with AUCs of 950-1,600 µM × min had 83.7% (95% CI: 73.3-95.5) event-free survival (EFS) compared with 55.0% (95% CI: 37.0-81.8) for patients with low or high exposure (p = 0.024). The logistic regression analysis results showed no association between transplant-related toxicities and the busulfan AUC (p > 0.05).Conclusions: The variability in busulfan CL was related to the NFM and Fmat, while busulfan V was related to the FFM. Preliminary analysis results suggested that a busulfan AUC of 950-1,600 µM × min was associated with better EFS in children receiving the 16-dose busulfan regimen.